Odpowiedzi

Najlepsza Odpowiedź!
2009-09-29T20:48:48+02:00
1- 2x+5 \ 3 =4 | *3
1-2x+5=12
-2x=12-5-1
-2x=6 | :(-2)
x=-3

-4(1\2x - 2)- 4 = 2(-x +2)
-2x+8-4=-2x+4
-2x+2x=4+4-8
0=0

2x(x-1) = 2(x-1) (x+3)
2x²-2x=2(x²+3x-x-3)
2x²-2x=2x²+6x-2x-6
2x²-2x²-2x+2x-6x+6=0
-6x+6=0
-6x=-6
x=1

x\2 - x\3 +1= 1\6(x+6)
x\2-x\3+1=1\6x+1 | *6
3x-2x+6=x+6
3x-2x-x=6-6
0=0

x-1\4 - x+1\2 = -x\4 | *4
4x-1-4x+2=-x
4x-4x+x=-2+1
x=-1

2009-09-29T20:49:11+02:00
1-2x+5/3=4
2x=-3+⁵/₃
6x=-9+5
x=-²/₃

-4(¹/₂x-2)-4=2(-x+2)
-2x+8-4=-2x+4
4=4
X∈R

2x(x-1)=2(x-1)(x+3)
2x²-2x=2x²+6x-2x-6
x=1

x/2-x/3+1=1/6(x+6) /×6
3x-2x+6=x+6
6=6
x∈R

x-¹/₄-x+¹/₂=-x/4 /×4
4x-1-4x+2=-x
x=-1
2009-09-29T22:19:39+02:00
1- 2x+5 \ 3 =4 | *3
1-2x+5=12
-2x=12-5-1
-2x=6 | :(-2)
x=-3

-4(1\2x - 2)- 4 = 2(-x +2)
-2x+8-4=-2x+4
-2x+2x=4+4-8
0=0

2x(x-1) = 2(x-1) (x+3)
2x²-2x=2(x²+3x-x-3)
2x²-2x=2x²+6x-2x-6
2x²-2x²-2x+2x-6x+6=0
-6x+6=0
-6x=-6
x=1

x\2 - x\3 +1= 1\6(x+6)
x\2-x\3+1=1\6x+1 | *6
3x-2x+6=x+6
3x-2x-x=6-6
0=0

x-1\4 - x+1\2 = -x\4 | *4
4x-1-4x+2=-x
4x-4x+x=-2+1
x=-1